IMPLEMENTASI PEMBELAJARAN LUGHAT KITAB MUHAWARAH TINGKAT WUSTHO DI PONDOK PESANTREN RAUDHATUT THALIBIN : STRATEGI, TANTANGAN, DAN SOLUSI - M. Sandri Ansari; Radiatun Nazwa; Irwanda Tri Saputra; Mursyidatul Awaliyah (STIT Darul Hijrah Martapura, 2025)
This study aims to examine in depth the implementation of lughat muḥāwarah learning at the Wustho level in the Islamic boarding school Raudhatut Thalibin. The research employed a descriptive qualitative approach to obtain a comprehensive understanding of the learning process as it occurs in its natural setting. Data were collected through direct classroom observations, in-depth interviews with teachers and students, and analysis of relevant documentation such as lesson plans and learning materials. The findings indicate that lughat muḥāwarah learning is implemented using a variety of interactive and communicative methods. These methods include paired dialogues to encourage direct communication, simulations of daily situations to connect learning with real-life contexts, role-playing activities to improve speaking fluency and confidence, and habituation programs that require students to use Arabic in their daily interactions. Such approaches help create a language-rich environment that supports students’ speaking skills. Several supporting factors contribute to the effectiveness of this learning process, including the availability of appropriate and relevant textbooks, strong teacher commitment, and the existence of special programs such as Arabic Day. However, the study also identifies inhibiting factors, such as students’ low self-confidence, limited opportunities for practice, and less-than-optimal learning motivation. Therefore, this study recommends increasing teacher creativity, maximizing the use of interactive learning media, and encouraging Arabic language practice beyond the classroom to achieve more optimal learning outcomes.